Isolectins of phytohemagglutinin are able to induce apoptosis in HEp-2 carcinoma cells in vitro - Kochubei, T.O.; Maksymchuk, O.V.; Piven, O.O.; Lukash, L.L. (Experimental Oncology, 2015)
Aim: To study the effects of total phytohemagglutinin (PHA) and its isolectins on cell death and apoptosis in human HEp-2 carcinoma cells and to analyze the possible molecular mechanisms of lectin induced apoptosis. Materials and Methods: The commercial preparation of the kidney beans (Phaseolus vulgaris) lectins and HEp-2 cells were used. Apoptosis index was determined using acridine orange and ethidium bromide staining. The expression levels of apoptosis mediator cleaved caspase-3 and proapoptotic Bax protein were studied by Western blot analysis. The gene expression levels were analyzed by qPCR. Results: PHA and its isolectins induced apoptosis in HEp-2 cells accompanied by the increased expression of caspase-3 cleaved form, with PHA-E being the most effective. The treatment of HEp-2 cells with PHA or its isolectins resulted in a marked increase of Bax on both mRNA and protein levels. Conclusions: PHA and its isolectins were shown to induce the apoptosis in human HEp-2 carcinoma cells via increasing proapoptotic protein Bax and activating caspases-3. Key Words: phytohemagglutinin, isolectins, apoptosis, caspase-3, Bax.